Conflict Management and Performance of Multigenerational Nurses at Haji Makassar Hospital - Patima; Marzah Genta Ramadhani; Syisnawati; Musdalifah; Syamsiah Rauf; Rahmi Damis; Aidah Fitriani; Rasdiyanah; Eny Sutria; Ani Auli Ilmi; Ilhamsyah; Ahmad J; Mariam Mohd Nasir (Universitas STRADA Indonesia, 2026)
Background: Nurse performance plays a crucial role in the success of healthcare. However, nurses' performance can be affected by conflicts in the workplace, including intergenerational conflicts arising from differences in age, experience, and communication styles. Conflicts that are not managed properly have the potential to reduce teamwork and the quality of nursing services. Objective: This study aims to determine the relationship between conflict management and the performance of multigenerational nurses at Haji Makassar Hospital. Methods: This study used a quantitative research design with a cross-sectional approach. The variables in this study are: conflict management as an independent variable and nurse performance as a dependent variable. The sampling technique used was non-probability sampling with the total sampling method. The sample consisted of 80 nurses who met the inclusion criteria. Data were collected using a questionnaire on conflict management and nurse performance and analyzed using the Somers'D statistical test. Results: The results showed that most of the multigenerational nurses had good conflict management (62.5%), and most also showed good performance (73.8%). The Somers'D statistical test revealed a p value of 0.020 (p < 0.05), which showed a significant relationship between conflict management and the performance of multigenerational nurses at Haji Makassar Hospital. Conclusion: This study shows that effective conflict management contributes to improved performance of multigenerational nurses. Therefore, strengthening conflict management strategies through improved intergenerational communication and teamwork is needed to support the quality of nursing services.